The Consolidation and Spread of Islam in South Africa (American Journal of Islam and Society, 2009)
Much has been written about Islam’s advent, entrenchment, and spread in specific regions of South Africa, and other writings cover its advent over the entire country. And yet no sufficient academic scrutiny of factors that have contributed to its consolidation and spread in recent times has been undertaken. By researching this issue, the problems and challenges confronting Islam at present and in the foreseeable future will be better appreciated. After presenting a brief synopsis of Islam’s advent South Africa, I assess how it was consolidated and then tackle its spread while underscoring specific successes and failures. Where necessary, the names of individuals are mentioned. The divergent nature of Islamic faith and practice is constantly stressed. The topic is a fascinating field of study in which sometimes contradictory forces strive for hegemony. Finally, a possible solution to this problem is presented.